HUBUNGAN PENGETAHUAN DAN KEPATUHAN IBU HAMIL MINUM TABLET FE DENGAN KEJADIAN ANEMIA DI WILAYAH KERJA PUSKESMAS RAWAT INAP SUBAN KABUPATEN TANJUNG JABUNG BARAT TAHUN 2025 - Novi Efriyanti; Sri Mulyati (Universitas Adiwangsa Jambi, 2025)
Anemia in pregnant women is a health problem that can lead to complications during pregnancy and childbirth. This study aims to determine the relationship between knowledge and compliance of pregnant women in taking Fe tablets with the incidence of anemia in the Work Area of Suban Inpatient Health Center, West Tanjung Jabung Regency in 2025. A quantitative method with a cross-sectional design was used, involving 55 respondents selected through purposive sampling. Data were analyzed using the chi-square test. The results showed a significant relationship between knowledge and compliance of pregnant women in taking Fe tablets and the incidence of anemia (p < 0.05). It is concluded that higher levels of knowledge and compliance in consuming Fe tablets are associated with a lower risk of anemia. Health workers are encouraged to continue providing education and motivation to pregnant women on the importance of regular Fe tablet consumption.